2017
DOI: 10.1002/ldr.2844
|View full text |Cite
|
Sign up to set email alerts
|

Crops and livestock under the sun: Obstacles to rural livelihood adaptations to hotter 21st century temperatures in eastern Senegal

Abstract: This article evaluates the proposition that farmers in dryland West Africa will be compelled by midcentury to shift household resources from crop to livestock production due to changing climate conditions. The article investigates the prospects for such a livelihood transition in the semiarid part of eastern Senegal, where downscaled statistical models indicate temperature increases of at least 2°, that will have substantially negative impacts on crop yields. Based on survey of 448 households and focus groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…In West Africa, climate change is expected to reduce crop production, compromising the food security of subsistence farmers, and rendering livelihoods based on natural resources more challenging, particularly in the Sahel zone ( 3 ). Recent studies in West Africa have shown that differences in age, gender, education, disability as well as livelihood diversification significantly influence levels of vulnerability to the effects of climate change ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In West Africa, climate change is expected to reduce crop production, compromising the food security of subsistence farmers, and rendering livelihoods based on natural resources more challenging, particularly in the Sahel zone ( 3 ). Recent studies in West Africa have shown that differences in age, gender, education, disability as well as livelihood diversification significantly influence levels of vulnerability to the effects of climate change ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…For local elites, however, it is politically more comfortable and convenient to blame global climate change than it is to trace crises to histories of underdevelopment (Rodney, 1973) and exploitative international systems (Davis, 2002, p. 11014), which (like climate change attributions) lead responsibility attributions back to the over‐developed counties (Ribot, 2014). To the extent that climate narratives have led to policies to guard against climate extremes, efforts have targeted things such as water retention or pumping, rather than policies that might support local security via agricultural prices, access to markets and credit, or social services (Brottem & Brooks, 2018; Ribot et al, 2020; Tschakert, 2007).…”
Section: Disasters and Responsibility Attributions: The Politics Of C...mentioning
confidence: 99%
“…Deste modo, alguns autores têm analisado os impactos nas regiões semiáridas, pois estas regiões concentram uma parcela importante da população vulnerável dependente da agricultura, como também, estas regiões estão em áreas em que há uma tendência de maiores efeitos negativos das mudanças climáticas sobre a produção agrícola, renda e inclusive segurança alimentar (BROTTEM & BROOKS, 2018;HASSAN, 2010;SIVAKUMAR, DAS & BRUNINI, 2005).…”
Section: Introductionunclassified